2012
DOI: 10.1177/1470320312444650
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of risk and interaction of single nucleotide polymorphisms at angiotensinogen locus causing susceptibility to essential hypertension: a case control study

Abstract: Introduction:The risk conferred by the variants and haplotypes of single nucleotide polymorphisms (SNPs) at human angiotensinogen (AGT) gene to essential hypertension (EHT) have been described in several populations with variations in the results attributed to their ethnicity. We attempted to evaluate the risk of -217G>A, -152G>A, -20A>C, -6G>A, T174M, M235T and 15241A>G polymorphisms at AGT locus along with the analyses of haplotype and epistatic interactions in causing susceptibility to EHT. Method: Two-hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 74 publications
3
9
0
Order By: Relevance
“…However, previous studies in south India mainly focus on limited gene of RAS [47, 48, 51]; thus we carried out a case-control study to systemically investigate the association between polymorphisms in RAS genes and essential hypertension. The present study identifies gender specific genetic variants in RAS genes that may play crucial roles in BP regulation and susceptibility for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies in south India mainly focus on limited gene of RAS [47, 48, 51]; thus we carried out a case-control study to systemically investigate the association between polymorphisms in RAS genes and essential hypertension. The present study identifies gender specific genetic variants in RAS genes that may play crucial roles in BP regulation and susceptibility for hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the attributed inconsistencies and the magnitude of low power to detect an association with individual SNPs can be improved using gene–gene interaction analysis 36 37. The epistatic evaluation in multifactorial disease like EH further increases the predictive accuracy of genotype–phenotype correlations 7.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent molecular epidemiology studies revealed that certain genetic variants are associated with susceptibility to hypertension. In particular, polymorphisms of genes, including the leptin receptor, angiotensinogen, cytochrome P450, vascular endothelial growth factor, adrenoceptor, ApoB, bradykinin beta 2 receptor, and apolipoprotein CIII, have been associated with the susceptibility to this disease (Charita et al, 2012;Fowdar et al, 2012;Gu et al, 2012;Hamedian et al, 2012;Li and Liu, 2012;Shin et al, 2012;Tang et al, 2012;Xi et al, 2012b). Similar to variants of other genes in the apolipoprotein family, apoE gene polymorphisms may also contribute to the occurrence of hypertension in various populations.…”
Section: Discussionmentioning
confidence: 99%